An Effectiveness Test Combination of Ethanol Extracts of Buas-buas Leaves (Premna serratifolia L.) and Sappan Wood (Caesalpinia sappan L.) as Topical Antiinflammatory Agent in Male White Rats (Rattus novergicus) - Isnindar; Purnamaputra, Alfred; Luliana , Sri (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Inflammation is the reaction of the immune system to tissue damage resulting from physical injury, harmful chemicals, or microbial agents. Steroid and non-steroid drugs are commonly used to treat inflammation, but long-term use can result in side effects, such as hormonal disorders and gastric ulcers. Buas-buas leaves and sappan wood has potential as traditional medicines, and based on empirical evidence, they utilize both plants as anti-inflammatory, antibacterial, antioxidant, antiallergic, and antiarthritic agents, as well as for the treatment of cardiovascular disorders, cough, and leprosy. Objective: This study aimed to evaluate the effect of combining 96% ethanol extracts from buas-buas leaves and sappan wood to deliver topical anti-inflammatory benefits. Methods: This research was experimental, using thirty male rats divided into six treatment groups: a negative control group with 2% carrageenan, Biocream® control group, a positive control group with Hydrocortisone Acetate, and three treatment groups receiving a combination of ethanol extracts from buas-buas leaves and sappan wood at concentrations of 1.67%, 2.5%, and 3.75%. The test compounds were administered after carrageenan injection. Measurement of skinfold thickness on the backs of the rats was conducted every hour for 6 h using digital calipers, and the difference in skinfold thickness of each rat, AUC value, and percentage of inflammation inhibition was calculated. Data analysis involved the Kolmogorov-Smirnov test and Levene's test to assess normality and homogeneity, respectively, and was subsequently followed by One-way ANOVA and a post-hoc test. Conclusion: The combination of ethanol extracts of Buas-Buas leaves and sappan wood can provide a topical anti-inflammatory effect, with the most effective concentration being 3.75% and an inflammation inhibition percentage of 32.77%.